Experimental and numerical study of bubbly flow and bubble size distribution produced by swirling flow bubble generator - Hilman Syaeful Alam; Muhammad Imam Arif; Tubagus Ahmad Fauzi Soelaiman; Priyono Sutikno; Anto Tri Sugiarto; Asep Yusuf (Results in Engineering)
This study used experiments and numerical simulations to investigate the two-phase flow characteristics and microbubble size distribution in a swirling flow bubble generator. A high-speed camera and Particle Image Velocimetry (PIV) were used to observe the flow and bubble size distribution. Computational Fluid Dynamics (CFD) simulations coupled with the Population-Balanced Method (PBM) were applied with transient solvers, a mixture model for two-phase flow, turbulent bubble aggregation, and Lehr breakup kernels. The results showed that increasing the ratio of water to gas flow rate (Qw/Qg) led to more microbubble formation, with an increase in intensity of 12–19 % when the water flow rate increased from 20 to 32 L/min. However, based on ANOVA results, the oxygen gas flow rate variation (0.5–1 L/min) had no significant effect. The CFD-PBM model successfully predicted this system's bubble size distribution and flow characteristics. The kinetic energy and pressure changes affected the bubble behavior in the swirl chamber. However, for a more detailed analysis of bubble interactions, high-resolution models such as the Eulerian-Lagrangian approach are required in further studies.